"Living more and struggling less": a qualitative descriptive study of patient experiences of physiotherapy informed by Acceptance and Commitment Therapy within a multidisciplinary pain management programme. (September 2022) - Aymerich, Katy; Wilczek, Angelika; Ratanachatchuchai, Soravis; Gilpin, Helen R.; Spahr, Nicolas; Jacobs, Clair; Scott, Whitney
Abstract: Objectives: Physiotherapists increasingly deliver treatment informed by cognitive-behavioural therapy, including Acceptance and Commitment Therapy (ACT), for persistent pain. This study explored patients' experiences of ACT-informed physiotherapy to better understand therapeutic processes and outcomes. Design: A qualitative descriptive study was conducted. Focus groups explored participants' experience of ACT-informed physiotherapy in the context of a pain management programme. Responses were audio recorded, transcribed verbatim, and analysed using a hybrid inductive-deductive reflexive thematic analysis. Setting: A single tertiary care pain management service. Participants: The sample consisted of fifteen patients from two treatment groups who completed an intensive multidisciplinary ACT-based pain management programme. Participants were included irrespective of their treatment response. Results: One overarching theme (living more and struggling less) and four interconnected themes were generated from the data: 1) awareness and openness help to approach physical activities flexibly; 2) from battling against to working with the body compassionately; 3) from narrow focus to curiosity, freedom, and expansion; and 4) social connection is a catalyst for openness and engagement. Conclusions: Participants experienced ACT-informed physiotherapy as helping them to live more and struggle less with pain; this occurred in the context of a psychologically flexible relationship with the physiotherapist and was catalysed by social connection. These findings should be seen as preliminary given the small number and relatively brief duration of focus groups conducted. Further research is needed to explore how principles within ACT-informed physiotherapy may support patients and clinicians to respond effectively to the challenges that persistent pain can bring.